THERMAL TREATMENT OF VARIOUS SAMPLES OF LOW-MOLECULAR-WEIGHT POLYETHYLENE – A BY-PRODUCT OF POLYETHYLENE PRODUCTION - Ochilov, Golibjon; Abdumalikov , Abdulaziz; Ummatov, Obidjon; Mamajonov, Bakhodirjon; Esonkulova, Nazirakhon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
A comparative thermal analysis was conducted on three industrial samples of low-molecular-weight polyethylene (LMWPE)—a by-product of polyethylene production—with the aim of determining optimal conditions for carbonization and subsequent activation. The study employed TGA/DSC methods (Ar, 10 °C/min) and laboratory-scale carbonization in a flow-through argon reactor, with gas sampling at specific temperature “windows” followed by GC analysis (TCD + FID). The results indicate that melting occurs in the range of approximately 30–150 °C with less than 1% mass loss; thermal degradation begins at 300–400 °C, with major decomposition occurring between 420–520 °C. The residual mass at 1000 °C was approximately 33% (LMWPE-1), 38% (LMWPE-2), and 53% (LMWPE-3), indicating differences in molecular architecture and suggesting LMWPE-3 as the preferred precursor in terms of carbon yield. Gas evolution trends showed a transition from C₃–C₁₇ olefins/paraffins (300–520 °C) to dominant H₂ and CH₄ evolution at higher temperatures, accompanied by increased aromaticity of the solid residue. It is recommended to limit the upper carbonization temperature to ~500 °C to avoid melting and coalescence, and to employ the 750–820 °C range as the optimal “window” for high-temperature treatment relevant to subsequent alkaline activation.